Review: deformation and optimisation crashworthiness method for foam filled structures - Djamaluddin,Fauzan (2019)
Abstract In this paper, we give overview of deformation modes for the uniform foam filled thin-walled structure such as circular tubes, square tubes, rectangular tubes, tapered tubes, hat tubes and cone tubes. Foam material is used as a reinforcing material on a thin wall tube which has potential as being a good energy absorber. This is evident from many of the studies undertaken on the crashworthiness performance and energy ab-sorption of the thin wall tube. Also, this paper presents a review of the current state of the art in computa-tional optimization methods applied to foam filled structures, offering a clear vision of the latest research advances in this field.